2021
DOI: 10.12911/22998993/131031
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of ZnO-Zeolite Nanocomposite for Photocatalytic Degradation by Ultraviolet Light

Abstract: The increasing growth of the textile industry does not only provide benefits in the economic sector but also has the potential to damage the environment, because it generates the dye wastewater which is hard to eliminate. Procion red is one of the synthetic textile dyes that is toxic to the aquatic environment and it needs to be processed properly. The photocatalytic method of processing dye wastewater is the most effective, because it can remove the harmful pollutants in the dye wastewater. This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
(12 reference statements)
3
14
0
Order By: Relevance
“…Generally it was observed that ZnO loaded catalyst had displayed higher porosity as compared to pure ZnO which leads to enhanced adsorption of the pollutant molecules and thus improving photocatalytic ability. The obtained textural properties of the Zno/Zeolite Na-A catalyst were in agreement with results from previous studies such as Gayatri et al, [16] who worked on ZnO/Zeolite Na-A and obtained SBET, pore size and pore volume of 95.98 m 2 /g, 44.2 Å and 0.08 cm 3 /g respectively. They attributed the obtained pore size to pore widening due to removal of impurities after the ZnO/zeolite activation treatment.…”
Section: Nitrogen Adsorption-desorption For Surface Area and Pore Sizesupporting
confidence: 91%
“…Generally it was observed that ZnO loaded catalyst had displayed higher porosity as compared to pure ZnO which leads to enhanced adsorption of the pollutant molecules and thus improving photocatalytic ability. The obtained textural properties of the Zno/Zeolite Na-A catalyst were in agreement with results from previous studies such as Gayatri et al, [16] who worked on ZnO/Zeolite Na-A and obtained SBET, pore size and pore volume of 95.98 m 2 /g, 44.2 Å and 0.08 cm 3 /g respectively. They attributed the obtained pore size to pore widening due to removal of impurities after the ZnO/zeolite activation treatment.…”
Section: Nitrogen Adsorption-desorption For Surface Area and Pore Sizesupporting
confidence: 91%
“…For example, the dispersion of Pt nanoparticles into mesoporous Co 3 O 4 was reported to increase the catalytic oxidative degradation efficiency toward methylene blue (MB) dye, with almost 100% removal after 60 min of treatment [ 64 , 65 ]. Similar results were recorded from supported ZnO nanoparticles using zeolite [ 66 , 67 ], supported iron nanoparticles using zeolite [ 68 , 69 ], and supported Au nanoparticles into TiO 2 and BiVO 4 [ 70 , 71 ]. Microporous and mesoporous solids were employed for supporting metal and metal oxide nanoparticles; some of them are noted to be low-cost supports such as zeolite, silica, graphene, carbon, C 3 N 4 , and clay minerals [ 72 , 73 , 74 , 75 , 76 ].…”
Section: Metal and Metal Oxide Nanoparticles In Aopssupporting
confidence: 73%
“…Among the used adsorbents, zeolite is a natural adsorbent with porous architectures. In addition to the traditional application of zeolite to soften water, it is used in catalytic processes, membrane separation, alternative zeolite processing, wastewater treatment, antimicrobial applications, construction, coating, pulps, and paper [ 27 , 28 , 29 , 30 , 31 , 32 ]. However, its dye adsorption capability is restricted by its compacted structure (low pore volume), which reduces its cationic exchange capacity and adsorption capabilities.…”
Section: Introductionmentioning
confidence: 99%